EKRANISASI NOVEL ASSALAMUALAIKUM BAITULLAH KARYA ASMA NADIA KE FILM ASSALAMUALAIKUM BAITULLAH SUTRADARA HADRAH DAENG RATU - Triyanti, Ayu; Irawan, Dody; Dwi Leoni, Tessa; Wahyusari, Ahada; Lolita, Asri; Musliha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the ekranisasi processes regarding plot, characters, and setting as the novel Assalamualaikum Baitullah by Asma Nadia was adapted into the film Assalamualaikum Baitullah directed by Hadrah Daeng Ratu. A qualitative descriptive method was employed to describe the research findings. The researcher served as the primary instrument of the study. The data consisted of the novel's text as well as scenes and dialogue transcripts from the film concerning the adaptation. Data collection was conducted using the documentation technique, involving the recording of information from the novel's text and the film's scenes and dialogue transcripts. Data analysis involved data reduction, data presentation, and conclusion drawing. The results indicate that the adaptation process involved changes in the form of reduction, addition, and variation regarding the plot, characters, and setting.The most dominant form of adaptation was the reduction of plot elements, carried out to align with the film's runtime